2023
DOI: 10.1108/mrr-10-2022-0726
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between job burnout and intention to change occupation in the accounting profession: the mediating role of psychological well-being

Abstract: Purpose This study aims to examine the relationship between job burnout, psychological well-being and intention to change occupation among accounting professionals. It focuses on the role of psychological well-being in explaining the link between job burnout and intention to change occupation. Design/methodology/approach Data were collected with the help of a structured questionnaire. The final sample includes 218 accounting professionals in the private sector. To test the hypothesized model in this study, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 82 publications
(101 reference statements)
1
4
0
Order By: Relevance
“…Furthermore, our findings align with the JD-R model, providing empirical evidence for the negative impact of job burnout on psychological well-being (Lizano, 2015). This supports the theoretical underpinnings of the JD-R model in explaining the dynamics of burnout and its consequences, particularly in relation to dimensions such as anxiety and depression (Çollaku et al , 2023).…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Furthermore, our findings align with the JD-R model, providing empirical evidence for the negative impact of job burnout on psychological well-being (Lizano, 2015). This supports the theoretical underpinnings of the JD-R model in explaining the dynamics of burnout and its consequences, particularly in relation to dimensions such as anxiety and depression (Çollaku et al , 2023).…”
Section: Discussionsupporting
confidence: 74%
“…This finding stands in contrast to the initial expectations of the study. Previous research by Çollaku et al (2023) demonstrated a significant positive relationship between burnout and the intention to change profession. This finding was further supported by Heinen et al (2013), who found that burnout heightened the intention to leave the profession among nurses in ten European countries.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations